Eastern Mediterranean climate change deduced from the Soreq Cave fluid inclusion stable isotopes and carbonate clumped isotopes record of the last 160 ka. (15th November 2021) - Matthews, A.; Affek, H.P.; Ayalon, A.; Vonhof, H.B.; Bar-Matthews, M.
Abstract: A fundamental issue in the interpretation of speleothem calcite δ 18 Occ records is the correct partitioning of the effects of temperature and water δ 18 O variations. This study explores the paleo-environmental evolution of the Eastern Mediterranean Sea (EMS) region using Soreq Cave speleothems in the last 160 ka, a period covering glacial MIS6 to the present, through the independent determinations of temperatures via carbonate clumped isotopes (Δ47 ) and fluid inclusion δ 18 Ow, δDw and d-excess values of cave water entrapped in the speleothems. The observed general agreement between the trends in water δ 18 Ow composition directly measured from fluid inclusions and calculated from Δ47 temperatures and δ 18 Occ support the robustness of the data. Δ47 temperatures, derived using a revised thermometer calibration that includes recent modifications in 17 O correction, vary from high values of 20–22 °C during interglacial periods to low values of 11–12 °C in cold glacial and stadial periods. Temperatures of 19–22 °C are observed during the time of deposition in the EMS of sapropel S5 in the last interglacial MIS5e period and sapropel S1 in the early Holocene, immediately following Terminations II and I, respectively. The Soreq Cave Δ47 temperatures generally agree with previously estimated EM sea surface temperatures, in support of the absence of a significant land-sea temperature gradient. Cave water δ 18 Ow values show large variations (from ∼-3 to −7.5‰), with high glacial and low interglacial values. These variations are largely explained by changes in Mediterranean Sea water composition due to glacial ice melting and freshwater input during sapropel periods, combined with the effect of rainfall amounts during interglacial periods. An analysis of relative timing shows that temperature rise precedes hydrological changes in the initial stages of Termination events. Fluid inclusion d-excess values show clear variations between values similar to the Global Meteoric Water Line during cold periods and values similar to the local Eastern Mediterranean Meteoric Water Line (EMMWL) in warm periods. Highlights: Clumped isotope thermometry and δ 18 Occ enable creation of cave water δ 18 Ow record. δ 18 Ow values derived from clumped isotopes agree with fluid inclusion measurements. Temperatures vary from interglacial values of 20–22 °C to 11–12 °C in glacial maxima. d-excess values vary between GMWL and EMMWL in cold and warm periods, respectively. Temperature rise controls δ 18 Occ change during the initiation of Terminations.